Tuning the Bioactivity of Tensioactive Deoxy Glycosides to Structure: Antibacterial Activity Versus Selective Cholinesterase Inhibition Rationalized by Molecular Docking1. Issue 8 (18th February 2013) - Martins, Alice; Santos, Maria S.; Dias, Catarina; Serra, Patrícia; Cachatra, Vasco; Pais, João; Caio, João; Teixeira, Vítor H.; Machuqueiro, Miguel; Silva, Marta S.; Pelerito, Ana; Justino, Jorge; et al.
Abstract: New octyl/dodecyl 2, 6‐dideoxy‐D ‐ arabino ‐hexopyranosides have been synthesized by a simple but efficient methodology based on the reaction of glycals with alcohols catalysed by triphenylphosphane hydrobromide, deprotection, regioselective tosylation and reduction. Their surface‐active properties were evaluated in terms of adsorption and aggregation parameters and compared with those of 2‐deoxy‐D ‐glycosides and 2, 6‐dideoxy‐L ‐glycosides. Deoxygenation at the 6‐position led to a decrease in the critical micelle concentration, and an increase in the adsorption efficiency (pC20 ) promoting aggregation more efficiently than adsorption. With regard to the antibacterial activity, dodecyl 2, 6‐dideoxy‐α‐L ‐ arabino ‐hexopyranoside was the most active compound towards Bacillus anthracis (MIC 25 μM ), whereas its enantiomer exhibited a MIC value of 50 μM . Both 2, 6‐dideoxy glycosides were active towards Bacillus cereus, Bacillus subtilis, Enterococcus faecalis and Listeria monocytogenes . In contrast, none of the 2‐deoxy glycosides was significantly active. These results and the data on surface activity suggest that aggregation is a key issue for antimicrobial activity. Beyond infection, Alzheimer's disease also threatens elderly populations. In the search for butyrylcholinesterase (BChE) selective inhibition, 2‐deoxy glycosides were screened in vitro by using Ellman's assay. Octyl 2‐deoxy‐α‐D ‐glycoside was found to be a BChE selective inhibitor promoting competitive inhibition. Docking studies supported these results as they pinpoint the importance of the primary OH group in stabilizing the BChE inhibitor complex. A size‐exclusion mechanism for inhibition has been proposed based on the fact that acetylcholinesterase (AChE) exhibits several bulky residues that hinder access to the active‐site cavity. This work shows how the deoxygenation pattern, configuration and functionality of the anomeric centre can tune physical and surface properties as well as the bioactivity of these multifunctional and stereochemically rich molecules. Abstract : Alkyl 2‐deoxy‐ arabino ‐hexopyranosides have been synthesized and their surface‐active and biological properties tuned by their deoxygenation pattern and anomeric configuration. Dodecyl 2, 6‐dideoxy‐α‐glycosides showed the highest antibacterial activity, whereas 2‐deoxy‐α‐glycosides exhibited selective BChE inhibition, rationalized by molecular docking.